The Influence of Service Quality, Product Quality, and Price on IndiHome Customer Satisfaction in Salatiga City - Adrian Nanda Pratama; Hanna Prillysca Chernovita (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2023)
PT Telekomunikasi Indonesia is one of the largest service or goods provider companies in Indonesia. PT Telekomunikasi Indonesia, which focuses on the fields of Telecommunication, Information, Media, Edutainment, and Services, which is shortened to (TIMES), prepares products such as Indihome and Wifi.ID to facilitate all Indonesian people. This study aims to analyze Indihome customer satisfaction, especially in the city of Salatiga by using a type of research method using a quantitative approach based on the dimensions of product satisfaction, price quality, service quality, on customer satisfaction. The research data used 113 data and were processed with SPSS software through validity, reliability, descriptive analysis and multiple linear regression. The results showed that the independent variable (X) studied, namely product satisfaction, price quality, service quality had an effect of 73.2%. on the dependent variable (Y), namely customer satisfaction, while the other 26.8% is influenced by other factors outside the variables studied. So it can be concluded that the current Indihome products in terms of product satisfaction, price quality, service quality are very good.